Heat capacity of liquids: A hydrodynamic approach - Bryk, T.; Scopigno, T.; Ruocco, G. (Condensed Matter Physics, 2015)
We study autocorrelation functions of energy, heat and entropy densities obtained by molecular dynamics simulations of supercritical Ar and compare them with the predictions of the hydrodynamic theory. It is shown that the predicted by the hydrodynamic theory single-exponential shape of the entropy density autocorrelation functions is perfectly reproduced for small wave numbers by the molecular dynamics simulations and permits the calculation of the wavenumber-dependent specific heat at constant pressure. The estimated wavenumber-dependent specific heats at constant volume and pressure, Cv(k) and Cp(k), are shown to be in the long-wavelength limit in good agreement with the macroscopic experimental values of Cv and Cp for the studied thermodynamic points of supercritical Ar.